The Effect of Information Technology on Value Chain of Iranian Exemplary Exporter Manufacturer Companies - Mahmood Naderi Bani; Mohammad Ali Feyzpoor; Ali Sanayei (تحقیقات بازار یابی نوین, 2013)
The fast and ever-increasing progress in Information Technology (IT) area and their role inhelping firms to improve their performance cause them to depend on IT day by day. At thesame time, few studies have been conducted in this area, so the mechanism and effects of ITon Iranian firm’s value chains are unclear. Therefore, it is necessary to study in this area. Thisstudy is a descriptive survey. The statistical population of the research is composed of Iranianexemplary exporter manufacturer companies that have elected since 2004 to 2010 by theTrade Promotion Organization of Iran. Data gathering instrument was questionnaire and pathanalysis technique has been used for the purpose of data analysis. The research has threemain hypotheses and three sub-hypotheses. The conceptual research model has four variablesincluding: IT process infrastructure, the speed desirability of value chain process and the costand accuracy of that. The findings indicate that the IT process infrastructure of firms hasdirectly effect on the speed and accuracy of the value chin processes. Moreover, IT hasindirect effect on cost desirability of value chain processes through effecting on speed of thatvalue chain.